4n-3(n+2)=5

Simple and best practice solution for 4n-3(n+2)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n-3(n+2)=5 equation:


Simplifying
4n + -3(n + 2) = 5

Reorder the terms:
4n + -3(2 + n) = 5
4n + (2 * -3 + n * -3) = 5
4n + (-6 + -3n) = 5

Reorder the terms:
-6 + 4n + -3n = 5

Combine like terms: 4n + -3n = 1n
-6 + 1n = 5

Solving
-6 + 1n = 5

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 1n = 5 + 6

Combine like terms: -6 + 6 = 0
0 + 1n = 5 + 6
1n = 5 + 6

Combine like terms: 5 + 6 = 11
1n = 11

Divide each side by '1'.
n = 11

Simplifying
n = 11

See similar equations:

| -3.2-2x=5.4 | | 3x^2=4 | | 8x-4x=20 | | .83p=.9375 | | 2y=3y+2 | | -4.5-6x=2.7 | | c+24(5)=3c | | -4m+7=-3 | | 3.7k=-4.44 | | 8-3(x-4-4)=4 | | -5+2x-3x=-8 | | 1.19y+7.33=3.84-0.04y | | 6o-12=2o+36 | | x^2-8x=4x-32 | | 6x^2-14x^5=0 | | 36-24t+3t^2=0 | | 5(2n-4)=6(5n-3) | | -1.3x=3.9 | | 8-2x+3+6x=4x-21+x | | 2c+7.5=6.2-3.2 | | 2.35z-7.78=0.97+8.88z | | 6(1+1x)=-6 | | 8-(-9)= | | z+(-5)=4 | | 3x-1=23 | | -2.29+1.21y=8.32+3.95y | | v+(-4)=4 | | 8.28z-3.41=0.65-1.37z | | 50-n= | | h+6=0 | | 3(x+5)-(3x+15)=0 | | 7x-10+4x=9x-6 |

Equations solver categories